THERAPY OF GIARDIASIS IN CHILDREN - Ibatova Sh. M.; Achilova F. A. (American Journals Publishing, 2024)
Giardiasis is an urgent problem in children, as its clinical manifestations are often masked by various variants of gastroenterological pathology, including functional disorders of the gastrointestinal tract, aggravating their course, syndromes of excessive growth of intestinal microflora in the small intestine, malabsorption, multivitamin deficiency, as well as the development of allergic diseases. At the same time, the lack of verification of the diagnosis does not allow for adequate therapy.
Keywords: Giardiasis, children, clinical variants, therapy.